Parental burnout, parenting social skills and parental monitoring: married and single mothers - Trivellato Ferreira, Amanda; dos Santos Elias, Luciana Carla (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Motherhood and parenting is accompanied by daily challenges and, given the characteristics of the process, parents can experience parental burnout; a syndrome resulting from intense exposure to stress, which may be continuous, recurrent or punctual. Burnout acts as a risk factor in the lives of parents and children, on the other hand educational social skills and parental monitoring can act as protection. Given this context, the present study aimed to verify and compare signs of parental burnout, educational social skills and parental monitoring in married and single mothers. This was a quantitative, descriptive, comparison study with a cross-sectional design. 40 mothers participated (5 solo), from a city in the interior of São Paulo. The instruments used were: Parental Burnout Inventory (PBA), Parental Monitoring Questionnaire (QMP), Parental Educational Social Skills Interview Script (RE-HSE-P) and Critério Brasil. The results showed single mothers who were more exhausted than married mothers, however, with a greater repertoire in Parental Educational Social Skills and Context Variables to deal with their children. It was concluded that preventive programs with single mothers and married mothers can help them and their children.